Pengaruh Profitabilitas, Ukuran Perusahaan, Kepemilikan Manajerial, dan Market Activity terhadap Internet Financial Reporting - Aminah Farhanah; Adam Zakaria; Gentiga Muhammad Zairin (Jurnal Akuntansi, Perpajakan dan Auditing, 2026)
This study examines the effect of profitability, company size, managerial ownership, and market activity on Internet Financial Reporting (IFR) among Kompas 100 companies on the Indonesia Stock Exchange, 2022–2025, using a quantitative approach. Through purposive sampling, 45 companies with 180 observations were obtained. IFR was measured using a 112-item index and analyzed with Stata Release 15 via panel data regression. Based on the Chow and Hausman tests, the selected model was the Fixed Effect Model with Cluster Robust Standard Error. Results show that company size has a significant negative effect on IFR, while profitability, managerial ownership, and market activity have no significant effect. Simultaneously, the four variables significantly affect IFR, with an R-squared within of 10.47%. This indicates that company size is the only factor influencing variation in IFR practices, while among Kompas 100 companies, whose disclosure is high and uniform, the other three variables are not yet determinants.